Design of high power LED-based UVA emission system and a photosensitive substance for clinical application in corneal radiation - Mota, Alessandro D.; Cestari, Andre M.; Oliveira, Andre O. de; Oliveira, Anselmo G. [UNESP]; Terruggi, Cristina H. B. [UNESP]; Rossi, Giuliano; Castro, Jarbas C.; Ligabo, Joao P. B.; Ortega, Tiago A.; Rosa, Tiago; Kane, M. H.; Jiao, J.; et al. (Spie-int Soc Optical Engineering, 2015)
This work presents an innovative cross-linking procedure to keratoconus treatment, a corneal disease. It includes the development of an ultraviolet controlled emission portable device based on LED source and a new formulation of a photosensitive drug called riboflavin. This new formulation improves drug administration by its transepithelial property. The UV reaction with riboflavin in corneal tissue leads to a modification of corneal collagen fibers, turning them more rigid and denser, and consequently restraining the advance of the disease. We present the control procedures to maintain UV output power stable up to 45mw/cm(2), the optical architecture that leads to a homogeneous UV spot and the new formulation of Riboflavin.
Keywords: Ultraviolet LED; Cross-linking; Keratoconus; Riboflavin; Transepithelial; PID control system for LEDs; Close loop system for LED; UV based Optical system